Motivation to become an entrepreneur in Finland : the case of Bangladeshi immigrants - Ahmed, Hasan (2018)
This paper describes the motivations in the starting of own business, difficulties and challenges faced by the Bangladeshi immigrant entrepreneurs in Finland and support services available for immigrant entrepreneurs in Finland. This thesis aims to capture the distinctive essence and identify the factors that motivate immigrant people to start their own business in a foreign country.